CHARACTERISTICS OF SOME HYDROLYTIC ENZYMES AND BIOPULPING POTENTIAL OF FUNGAL ISOLATES FROM SELECTED WOOD SAMPLES IN SOUTHWESTERN NIGERIA (2014)
Pulping industry is both labour and energy intensive but in Nigeria, electricity supply is unstable. This has contributed to the near collapse of the Nigerian paper and pulp industry despite the rich forest resources in southwestern Nigeria. Use of alternative energy sources such as electricity generating sets further increases production cost. It therefore, becomes pertinent to seek alternative approach aimed at reducing mechanical pulping duration and improving pulp characteristics. The aim of the study was to characterise major hydrolytic enzymes of native fungi from selected wood samples and evaluate their biopulping potential. Chipped samples of three local woods (Anogeissus leiocarpus, Gmelina arborea and Terminalia superba) from Ekiti, Lagos, Ogun, Ondo, Osun and Oyo States were made to undergo spontaneous degradation. Thereafter, fungi were isolated, identified and screened for cellulase and hemicellulase production. Isolates selected based on maximal enzyme activities were used to produce cellulases (glucanase and glucosidase) and hemicellulases (mannanase and xylanase) with the chips as substrates. Kinetic, molecular and biochemical properties of partially purified hemicellulases were determined and optimised using standard methods. Chipped wood samples were subjected to treatments with fungal isolates singly and in combination for six weeks. Treated wood samples and pulp were evaluated fortnightly for changes in cellulose, hemicellulose, lignin and ash contents, tensile strength, fibre length and strength. Data were analysed using descriptive statistics and ANOVA at p = 0.05. Five hundred and twenty-six fungal isolates were obtained and identified as Aspergillus flavus(13), Aspergillus niger(125), Rhizopus spp(79). Lasiodiplodia theobromae(10), Penicillium purpurogenum(25), Fusarium chlamydosporium(37), Fusarium oxysporum(30), Fusarium compactum(25), Trichoderma harzianum(75), Trichoderma reesei(88) and Emericella nidulans(19). Aspergillus niger, F. compactum, T. harzianum and T. reesei were selected for enzyme production. Highest production of cellulase was 12.72U/gm±0.11 on A. leiocarpus by T. reesei. Best producer of mannanase was A. niger with 15.50U/gm±0.01 on G. arborea while highest xylanase production of 28.93U/gm±0.12 was by F. compactum on A. leiocarpus. Kinetic properties of xylanase was Vmax 1.402U/min/ml and Km 1.804U/ml with molecular weight of about 90kDa and that of mannanase was Vmax 0.754U/min/ml, Km 1.364U/ml and molecular weight was between 53 and 65kDa. Optimum xylanase activity was at 55oC and pH 5.5 while mannanase was at 30oC and pH 5.5. There was significant reduction in hemicellulose (45-27%) and lignin (20-15%) in treated wood compared to untreated samples. Gmelina arborea singly treated with F. compactum gave best result: cellulose, hemicellulose, lignin and ash were reduced by 14.1, 18.9, 4.1 and 4.7 % respectively; while tensile strength, fibre length and strength improved respectively by 6.4, 4.3 and 6.5 %. These conformed to Technical Association of Paper and Pulp Industries standard. Treatment of T. superba with combination of F. compactum and T. harzianum however, reduced cellulose, hemicellulose, lignin and ash by 20.7, 39.4, 11.9 and 10.6 % respectively, giving a better result than that obtained with single treatment. Fungal enzyme treated wood samples attained pulp characteristics that met required biopulping standard. Thus, native fungi may be employed for biopulping of common woods in Nigerian paper and pulp industries.